2018
DOI: 10.1021/acs.energyfuels.8b02845
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dioxide/Brine, Nitrogen/Brine, and Oil/Brine Wettability of Montmorillonite, Illite, and Kaolinite at Elevated Pressure and Temperature

Abstract: Wettability of CO2/brine/clay is one of the most important parameters in assessing CO2 storage capacities and containment security. Despite its importance, the literature data in this context are very limited. We thus systematically measured montmorillonite, illite, and kaolinite wettability for CO2/brine, nitrogen/brine, and nitrogen/oil systems at various pressures (5, 10, 15, and 20 MPa) and temperatures (305 and 333 K). The zeta potential of each clay mineral was also measured to investigate its link to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(37 citation statements)
references
References 72 publications
3
31
0
Order By: Relevance
“… 40 Under reservoir conditions, illite and kaolinite were reported to be hydrophilic in previous research studies. 41 However, the result of molecular dynamic simulation suggested that kaolinite was hydrophobic. 42 Pan et al also found that the presence of kaolinite made the contact angles of brine on the quartz increase in CH 4 and CO 2 environments at low temperature.…”
Section: Results and Discussionmentioning
confidence: 99%
“… 40 Under reservoir conditions, illite and kaolinite were reported to be hydrophilic in previous research studies. 41 However, the result of molecular dynamic simulation suggested that kaolinite was hydrophobic. 42 Pan et al also found that the presence of kaolinite made the contact angles of brine on the quartz increase in CH 4 and CO 2 environments at low temperature.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The compacted cylindrical samples (diameter of 3.8 cm and length of 1 cm) were removed from the cell after one week and then dried in an oven (50°C) for 48 h. All samples were compacted to the same porosity level of 15% and the grain size of montmorillonite, illite and kaolinite was about 75 μm. 27 The particle size of individual clay grain is generally < 2 or < 4 μm. [47][48][49] The compaction apparatus used is illustrated in Figure 1 and details of the samples are provided in Table 1.…”
Section: Methodology Sample Preparationmentioning
confidence: 99%
“…The detailed experimental setup has been described previously. 27,[54][55][56][57][58][59] Synthetic brine of 20 wt% NaCl and 1 wt% KCl, with mass fraction purities ≥0.99; see Table 1, in deionised water, was used in these measurements. The substrate was inserted inside the cell at a set temperature (333 K).…”
Section: Contact Angle Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings showed that the highest adsorption was observed with the 50–50 blend, and the adsorption behavior was best represented by the Langmuir isotherm. Fauziah et al [ 8 ] reported the effect of CO 2 , brine, oil, and nitrogen on the wettability of montmorillonite, illite, and kaolinite at elevated pressures. The findings showed that in the presence of CO 2 , montmorillonite had the highest water contact angle followed by illite and then kaolinite.…”
Section: Introductionmentioning
confidence: 99%